Freire's dialogues in the socio-labor perspective of museums: transformations and perspectives on the ethics of the museologist (Cadernos de Sociomuseologia, 2023)
Some aspects of the Museologist's Code of Professional Ethics are discussed based on Paulo Freire's thinking. The methodological bias rescues classic texts by Freire, bringing reflections about professional performance. The study situates a bibliographic research, after surveying the material and textual, thematic, interpretative and problematization analysis. In the result, there are discussions that reflect the labor dilemmas, extracting subsidies for dialogic and formative constructs that support the material, informational and communicational competences of professionals. It is concluded that museum professionals have a mission based on ethical principles and museum activities promote ways and opportunities in favor of critical thinking, social responsibility, scientific thinking necessary for the work and the symbolic mediation of the changes that have taken place in recent years. Keywords: Ethical aspect. Code of ethics. Museologist. Ethical-political thinking. Social responsability.